PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE LISTENING TEAM TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII MTs THAMRIN YAHYA RAMBAH HILIR - Sari, Anita; -, Arcat; Afri, Lusi Eka (Universitas Pasir Pengaraian, 2015)
This research aims to determine the effect of cooperative learning model Listening Team on MathematicsLearning Outcomes Grade VIII MTs Thamrin Yahya Rambah Hilir. This research is a Quasi-Experiment. Thesampling technique used was simple random sampling, which means a simple random sample. The sample inthis research is class VIII-1 and VIII-2, in which the class VIII-2 as the experimental class using cooperativelearning model Listening Team and class VIII-1 as a control class with conventional learning. The instrumentused was a form of essay test. The hypothesis testing using test calculation results obtainedis4.353 > 2.0590 for = 0.05. Because, then H0 is rejected and H1 is accepted. Thus there is theeffect of cooperative learning model Listening Team on mathematics learning outcomes eighth grade students ofMTs Thamrin Yahya Rambah Hilir 2014/2015.